PERANCANGAN DISPLAY PERHIASAN UNTUK MENINGKATKAN KEMUDAHAN MEMBAWA DAN MENATA PRODUK DALAM PERSIAPAN PAMERAN: JEWELRY DISPLAY DESIGN TO INCREASE THE EASE OF CARRYING AND ARRANGING PRODUCTS IN PREPARATION FOR AN EXHIBITION - Daniel Agung Kristiawan; Tri Putro, R. Tosan; Koniherawati (Jurnal Dimensi Seni Rupa dan Desain, 2024)
Product exhibitions are a very effective strategy in helping Small and Medium Enterprises (SMEs). Data from the Ministry of Tourism and Creative Economy in 2019 shows the significant role of jewelry in the economy, reaching 31.5%. Design goals involved portability, dual function as storage, modularity, and aesthetics. The research method used is qualitative with data triangulation techniques from observation, interviews and documentation. Data analysis was carried out by considering the needs of jewelry exhibition displays. The design uses the SCAMPER method and design thinking with a focus on practical and creative solutions. The research results showed obstacles such as a less sturdy structure, display weight, difficulty in arranging, and long preparation time. Design recommendations involving portable, product storage, collapsible and modular displays aim to increase the ease of preparing exhibitions and attract consumer attention.